Congenital dislocation of shin bones: treatment tactics - Shomuqimov Shukhrat Abdushukurovich; Fayzimatov Muzaffar Agzamovich; Jalolov Khabibullo Abdinabi ugli; Sodikov Sardor Abdunabievich (Zien Journals, 2024)
Purpose is to analyze the treatment of congenital dislocation of shin splints
Keywords: Purpose; analyze; congenital